Implementing Higher Order Thinking Skills (HOTS) in Arabic Language Learning: A Case Study on Critical Thinking Development at an Indonesian Islamic Junior High School - Maulia Yasminah Zakiyyah; Maskud Maskud; Asep Maulana (Abjadia : International Journal of Education, 2026)
This study aims to examine the application of Higher Order Thinking Skills (HOTS) strategy in Arabic language learning at SMP Plus Darus Sholah Jember and its impact on the development of students' critical thinking skills. By using a qualitative approach and case study method, data were obtained through observation, interviews, and documentation. The results show that HOTS strategies are implemented through cooperative learning models, the use of interactive media such as Kahoot, Quizizz, and crossword puzzles, as well as group projects based on analysis and creation. This strategy succeeded in creating an active, collaborative, and fun learning atmosphere, which encouraged students to develop the ability to analyze, evaluate, and create new information in Arabic. Specifically, the findings reveal that students demonstrated improvement in analyzing simple Arabic texts, were able to formulate questions and arguments in Arabic during group discussions, and showed increased ability in creating short written compositions based on given themes. In addition, teachers play an active role in modifying teaching materials to fit the principles of HOTS, although the limited HOTS content in textbooks is a challenge. This study concludes that HOTS-based learning contributes greatly to forming students who think critically, creatively, and adaptively to global challenges. The results of this study are expected to be a reference for educators in designing Arabic learning strategies that are more relevant to the demands of the modern era.